2011
DOI: 10.1083/jcb.201103117
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane segments of nascent polytopic membrane proteins control cytosol/ER targeting during membrane integration

Abstract: Vastly different folded transmembrane segments of nascent multispanning membrane proteins each induce structural changes in the ribosome tunnel and translocon that target the loops of the growing polypeptide alternately into the cytosol or ER lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…For in vitro transcription, the tatA or tatA-NTstrep regions in the corresponding pGEM constructs were amplified using the pGEMrecognizing primers pGEM-5-F (5'-CCC AGT CAC GAC GTT GTA AAA CG-3') and pGEM-5-R (5'-CTT CCG GCT CGT ATG TTG TG-3'), and the purified PCR-product was used as template for SP6 RNA-polymerase according to the suppliers protocol (NEB). Translation was done according to standard protocols (62).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vitro transcription, the tatA or tatA-NTstrep regions in the corresponding pGEM constructs were amplified using the pGEMrecognizing primers pGEM-5-F (5'-CCC AGT CAC GAC GTT GTA AAA CG-3') and pGEM-5-R (5'-CTT CCG GCT CGT ATG TTG TG-3'), and the purified PCR-product was used as template for SP6 RNA-polymerase according to the suppliers protocol (NEB). Translation was done according to standard protocols (62).…”
Section: Methodsmentioning
confidence: 99%
“…TatA variants were inserted into inverted membrane vesicles (IMVs) prepared from E. coli strain DADE/pBW-tatBC (52) by employing wheat-germ extract-based in vitro translation according to the protocol of Lin et al (62), but in the presence of IMVs (4 OD280) and with 600 pmol/ml tetramethylrhodamine (TMR)-cysteinetRNA Cys .…”
Section: In Vitro Reconstitution Of Cysteine-labeled Tata Into Invertmentioning
confidence: 99%
“…Time-resolved Spectral Measurements-Fluorescence lifetimes were measured as detailed in Lin et al (25). The background phase and modulation data from a sample lacking NBD were subtracted from an equivalent NBD-containing sample that was prepared in parallel (26).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the ribosome was implicated in influencing the translocon with respect to TM integration and pore sealing (e.g., refs. [16][17][18]. Molecular dynamics (MD) analysis suggested that modulation of the channel's gating kinetics is controlled by the TM's hydrophobicity (19)(20)(21).…”
mentioning
confidence: 99%